2018
DOI: 10.4317/medoral.22294
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia, thirst, sodium gradient and inter-dialytic weight gain in hemodialysis diabetic vs. non-diabetic patients

Abstract: BackgroundIn hemodialysis (HD) patients, xerostomia and hyposalivation may intensify sensations of thirst, and contribute to the intake of fluids and excessive inter-dialytic weight gain (IWG). Since IWG is regarded to be higher in diabetic patients than in non-diabetics HD enhancing their mortality, it is crucial to define plausible underlying causes. Therefore, the study investigates factors contributing to the increased IWG in diabetic HD patients.Material and MethodsThe study included 97 HD patients (38 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Bruzda‐Zwiech et al showed that the predialysis sodium level was associated with hyposalivation, and XI was associated with IDWG (23). In another study, the same authors determined that hyposalivation, DTI, and XI were significantly higher in diabetic patients compared to nondiabetic HD patients, and increased IDWG was associated with the predialysis sodium level (41). Unlike other studies, we used predialysis session POsm, and observed that POsm was negatively correlated with IDWG.…”
Section: Discussionmentioning
confidence: 99%
“…Bruzda‐Zwiech et al showed that the predialysis sodium level was associated with hyposalivation, and XI was associated with IDWG (23). In another study, the same authors determined that hyposalivation, DTI, and XI were significantly higher in diabetic patients compared to nondiabetic HD patients, and increased IDWG was associated with the predialysis sodium level (41). Unlike other studies, we used predialysis session POsm, and observed that POsm was negatively correlated with IDWG.…”
Section: Discussionmentioning
confidence: 99%
“…The salivary flow is significantly decreased in patients receiving hemodialysis typically by 20‐55% (Figure ). In some patients, severe hyposalivation (saliva secretion <0.1 mL/min) or even absent salivation has been observed . Hyposalivation is often more severe in the presence of diabetes .…”
Section: Pathogenesismentioning
confidence: 99%
“…Two studies have clearly demonstrated that xerostomia is significantly associated with greater IDWG. The adverse outcomes of high IDWG have been well documented making xerostomia, at least indirectly, a significant mortality risk.…”
Section: Consequencesmentioning
confidence: 99%
“…There is some evidence that there is a positive correlation between xerostomia (hyposalivation) and IDWG [ 6 , 7 , 8 ]. A patient with more serious xerostomia experiences an increase in IDWG because of the increased fluid intake [ 9 ].…”
Section: Introductionmentioning
confidence: 99%